The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.psj.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of eggshell quality by dietary N-carbamylglutamate supplementation in laying chickens

Abstract: Egg quality defects seriously reduce the quality grade and increase egg breakage in egg marketing activities. In this study, the effect of N-carbamylglutamate ( NCG ) on eggshell quality was investigated by evaluating calcium absorption and calcification in laying hens. A total of 30 newly hatched female Hy-Line chicks were randomly assigned to the control group (basal diet) and treatment group (basal diet supplemented with 1% NCG). At 25 wk, eggs from each group were obtained to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
(28 reference statements)
2
23
0
Order By: Relevance
“…It has been previously reported that NCG, an activator of carbamoyl phosphate synthase-1 and pyrroline-5 carboxylate synthase in the ornithine cycle, increases the synthesis of endogenous arginine ( 56 ) and promotes the process of ovarian tissue angiogenesis to provide adequate nutrients and oxygen, and favorable conditions for follicle growth and development ( 24 , 25 ). Dietary supplementation with NCG has also been reported to increase blood estradiol concentrations in yaks ( 25 ) and chickens ( 57 ). Supplementation of NCG also promoted cell proliferation and inhibited apoptosis of pig placental trophoblast cells ( 58 ), and stimulated cell proliferation of bovine granulosa cells ( 59 ), both of which can synthesize estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that NCG, an activator of carbamoyl phosphate synthase-1 and pyrroline-5 carboxylate synthase in the ornithine cycle, increases the synthesis of endogenous arginine ( 56 ) and promotes the process of ovarian tissue angiogenesis to provide adequate nutrients and oxygen, and favorable conditions for follicle growth and development ( 24 , 25 ). Dietary supplementation with NCG has also been reported to increase blood estradiol concentrations in yaks ( 25 ) and chickens ( 57 ). Supplementation of NCG also promoted cell proliferation and inhibited apoptosis of pig placental trophoblast cells ( 58 ), and stimulated cell proliferation of bovine granulosa cells ( 59 ), both of which can synthesize estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Hens were sacrificed after anesthesia, and the ovaries were separated for collection of small white follicle ( SWFs ) (2–4 mm). Composition and nutrient levels of basal diet is the same as that in a published article ( Ma et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chemically speaking, an ES from a hen has 65.6 percent water, 11.8 % proteins, 11 % fat, and 11.7 % ash. Chemically, ES powder is made up of 21.2 % carbon, 0.93 % magnesium oxide, 76.9 % calcium oxide, 0.42 % porosity, 0.02 % iron oxide, and 0.11 percent sodium oxide [22][23][24][25] (Figure 1). ESs also contains 0.3 % phosphorus, which is found in little amounts but is particularly beneficial for regenerating hen bones.…”
Section: Nutritional Profile Of Essmentioning
confidence: 99%
“…This can boost the absorption of micro minerals, such as calcium, because calcium is converted to an ionic form in an acidic environment, making it more soluble and accessible. The shortchain fatty acids produced during the prebiotic fiber fermentation process, along with the acidic environment they create, cause the mucosal cells to swell, which increases the surface area of the intestine and enhances calcium absorption [18][19][20][21][22][23][24][25].…”
Section: Prebiotics Probiotics and Synbioticsmentioning
confidence: 99%
See 1 more Smart Citation